Ataxia, dystonia and myoclonus in adult patients with Niemann-Pick type C. Issue 1 (December 2016) - Koens, L.; Kuiper, A.; Coenen, M.; Elting, J.; de Vries, J.; Engelen, M.; Koelman, J.; van Spronsen, F.; Spikman, J.; de Koning, T.; Tijssen, M.
Abstract Background Niemann-Pick type C (NP-C) is a rare autosomal recessive progressive neurodegenerative disorder caused by mutations in the NP-C 1 or 2 gene. Besides visceral symptoms, presentation in adolescent and adult onset variants is often with neurological symptoms. The most frequently reported presenting symptoms of NP-C in adulthood are psychiatric symptoms (38 %), cognitive decline (23 %) and ataxia (20 %). Myoclonus can be present, but its value in early diagnosis and the evolving clinical phenotype in NP-C is unclear. In this paper we present eight Dutch cases of NP-C of whom five with myoclonus. Methods Eight patients with genetically confirmed NP-C were recruited from two Dutch University Medical Centers. A structured interview and neuropsychological tests (for working and verbal memory, attention and emotion recognition) were performed. Movement disorders were assessed using a standardized video protocol. Quality of life was evaluated by questionnaires (Rand-36, SIP-68, HAQ). In four of the five patients with myoclonic jerks simultaneous EEG with EMG was performed. Results A movement disorder was the initial neurological symptom in six patients: three with myoclonus and three with ataxia. Two others presented with psychosis. Four experienced cognitive deficits early in the course of the disease. Patients showed cognitive deficits in all investigated domains. Five patients showed myoclonic jerks, including negative myoclonus. In all registered patients EEG-EMG coherence analysis and/or back-averaging proved a cortical origin of myoclonus. Patients with more severe movement disorders experienced significantly more physical disabilities. Conclusions Presenting neurological symptoms of NP-C include movement disorders, psychosis and cognitive deficits. At current neurological examination movement disorders were seen in all patients. The incidence of myoclonus in our cohort was considerably higher (63 %) than in previous publications and it was the presenting symptom in 38 %. A cortical origin of myoclonus was demonstrated. Our data suggest that myoclonus may be overlooked in patients with NP-C. All patients scored significantly lower on physical domains of HRQoL. Symptomatic treatment of movement disorders may improve physical functioning and subsequently HRQoL.